2016
DOI: 10.1177/0020764016682361
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to suicidal behaviors: A common suicide risk factor or a personal negative life event?

Abstract: Results showed no validity for ESB as a common risk factor for suicidality or other psychopathology, or as a latent trait. ESB showed evidence as a personal negative life event with individual effects and interpretations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Although convergent validity was supported, the relation between suicidal exposure and suicidal behavior remains equivocal in the literature. Our findings were consistent with past work showing positive associations of suicidal exposure with suicidal behavior (e.g., Kimbrel et al, 2016;Stanley et al, 2015;Ventrice et al, 2010) but inconsistent with past work showing null or negative associations of exposure with suicidal behavior (Burke et al, 2010;Harris & Bettiol, 2017;Mercy et al, 2001). The limited number of suicide attempts in the present sample precluded examination of differential associations between the exposure types and SI and attempts.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although convergent validity was supported, the relation between suicidal exposure and suicidal behavior remains equivocal in the literature. Our findings were consistent with past work showing positive associations of suicidal exposure with suicidal behavior (e.g., Kimbrel et al, 2016;Stanley et al, 2015;Ventrice et al, 2010) but inconsistent with past work showing null or negative associations of exposure with suicidal behavior (Burke et al, 2010;Harris & Bettiol, 2017;Mercy et al, 2001). The limited number of suicide attempts in the present sample precluded examination of differential associations between the exposure types and SI and attempts.…”
Section: Discussionsupporting
confidence: 66%
“…For example, hearing about a single instance of suicide likely has very different implications on one's suicide risk compared with multiple instances of witnessing suicide deaths. Prior studies also used a mix of quantitative and qualitative measures of exposure, none of which were validated (Burke et al., 2010; Harris & Bettiol, 2017; Kimbrel et al., 2016; Mercy et al., 2001; Stanley et al., 2015; Ventrice et al., 2010). Additionally, measures that distinguish exposure types were rare, with only three known studies examining multiple exposure types (e.g., direct exposure vs. indirect exposure; Burke et al., 2010; Ventrice et al., 2010; Wolford-Clevenger et al., 2018).…”
Section: Purpose and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, some researchers have measured suicidal exposure by administering multiple item measures. For example, Harris and Bettiol (2017) asked participants if they knew a family member or friend who died by or attempted suicide. Pirelli and Jeglic (2009) developed a measure that assesses the frequency of exposure to death of various causes, including suicide, and relationship to the deceased.…”
mentioning
confidence: 99%
“…A case–control study demonstrated that exposure to suicide attempts and deaths was lower among individuals who made a near lethal attempt as compared with controls (Mercy et al, 2001). Additionally, exposure to suicide attempts and deaths of friends or family was not associated with a combined measure of suicide ideation and attempts (Harris & Bettiol, 2017). Finally, exposure to suicide threats was not associated with suicide attempt history (Burke et al, 2010).…”
mentioning
confidence: 99%